Ketorolac and pethidine in post-operative pain relief - Uddin, Md. Burhan; Hossain, A. K. M. Mosharrof; Alam, Meer Mahbubul; Hossain, A. Z. M. Shakhawat (Bangladesh Journal of Pharmacology, 2007)
The study was designed to compare the analgesic efficacy and safety of ketorolac and pethidine in pain relief after major surgeries. A prospective, interventional study was conducted on 71 patients under-going major surgical intervention. Thirty six patients received ketorolac (15 mg, intramuscularly 6 hourly) and the rest 35 patients received pethidine (100 mg, intramuscularly 6 hourly) for 48 hours post-operatively. Analgesic efficacy and safety of ketorolac were compared with that of pethidine after 1, 6, 12, 24, 32 and 48 hours of drug administration. Analgesic efficacy was measured using Visual Analogue Scale (VAS) and Verbal Rating Scale (VRS). Safety of the drugs was assessed by using sedation score and also recording adverse drug events. Ketorolac showed equianalgesic effect as pethidine estimated by VAS score at 12th and 48th hour and by VRS score at 1st and 48th hour of post-operative period. In other periods of observation, pethidine exhibited better analgesic effects than ketorolac. Ketorolac was better tolerated than pethidine and had less adverse effects compared to pethidine. This study showed that post-operative pain during the first 48 hours can be relieved by either ketorolac or pethidine. Ketorolac appeared safer than pethidine while pethidine appeared more effective analgesic than ketorolac in the management of post-operative pain. Further studies including double-blind randomized trial have been suggested to confirm the present study.